The mechanism of divine attitude in realizing the spiritual happiness and spiritual health from the viewpoint of the Qur'an, with an emphasis on the verse of grace and mercy of divine (Younis / 58) - s s; s s; seyedmajid nabavi (پژوهش نامه معارف قرآنی, 2021)
One of the needs of human beings is happiness and spiritual health. Happiness and spiritual health depend on the quality of recognition, tendency and behavior and on the type of individual’s attitude. Happiness and spiritual health are affected by various factors including the attitude of man to the universe. The main purpose of this paper is to investigate the mechanism of the impact of knowledge on the realization of happiness and spiritual health from the perspective of verses and narratives. The study adopted a descriptive-analytical research method and the library information data collection method. Research showed that, from the Quran’s point of view, God’s attitude is the important factor in human mental health and happiness, which, with the consent of the past and the creation of confidence in the future, will make happiness. People either feel grief over the past or are worried about the future which has not arrived yet. Hence, in the pattern of spiritual happiness, the believers see their future and past governed by God, and they do not have any grief over the past and the fear of the future, and will remain calm and happy to what God has ordered.